Market Dynamics: A Classical Approach to Security Price Movements (Global Journal of Science Frontier Research, 2017)
The recently introduced Market Dynamics method demonstrates parallelisms between security price indicators and their physical counterparts. Specifically, the security price is viewed as a potential energy density, and events such as earnings releases as forces that affect security prices. This dynamic representation of security price movements is extended and applied towards developing an event driven approach for measuring security price movements and the associated price charts. A conservation of capital principal further underlines the central role of capital flow in the formation of support levels. This classical approach to security price movements enables access to a vast pool of existing scientific knowledge and opens new insights into analyzing security price movements with potential applications in the fields of finance and investment management.
Keywords: security; price; dynamic; movement; capital; money flow; conservation; support; divergence